Bacterial vaginosis in early pregnancy and birth outcomes: Evidence from a prospective cohort in the middle belt of Ghana - Dennis Gyasi Konadu; Alex Kwame Owusu-Ofori; David Kwame Dosoo; Zuwera Yidana; Gladys Matuamo Ngo; Philomina Nkansah Nfum; Richard Joshua Tetteh; Dennis Adu-Gyasi; Kwaku Poku-Asante (PLoS ONE, 2026)
Background Bacterial vaginosis (BV) is highly prevalent in women of African origin and has been associated with adverse birth outcomes (ABO), particularly preterm birth (PTB). However, evidence from sub-Saharan Africa remains limited, and while a previous study conducted in this area examined the prevalence of BV, its impact on pregnancy outcomes was not assessed. This study assessed the prevalence and risk factors of BV in early pregnancy and examined its association with ABO in the middle belt of Ghana. Methods This analysis was nested within a prospective cohort of pregnant women in the Kintampo North Municipality and Kintampo South District. Pregnant women <20 weeks’ gestational age were screened, consented, enrolled and followed through delivery until one year after birth. At enrolment, sociodemographic, behavioural, and obstetric data were collected, along with biological samples, including vaginal swabs for Gram staining and Nugent scoring. BV status was categorized as BV-negative (0–6) or BV-positive (7–10) and ABO included PTB (<37 weeks), low birthweight (LBW < 2.5 kg), and foetal loss. Data were double-entered in REDCap and analysed in R. Associations between BV and ABO were assessed using chi-square tests, and logistic regression was used to identify risk factors for BV. Results Of 1,180 pregnant women enrolled, 355 (30.1%) were BV-positive. PTB (9.9% vs. 8.7%; p = 0.50), LBW (13.8% vs. 12.0%; p = 0.39), and foetal loss (4.5% vs. 2.8%; p = 0.14) were all higher among BV-positive women, but none reached statistical significance. Younger age and unmarried status were associated with BV. Unmarried women (AOR 1.63; 95% CI: 1.20–2.22) and those reporting one sexual encounter per week (AOR 1.55; 95% CI: 1.01–2.37) had increased odds of BV. Conclusions BV is highly prevalent in early pregnancy in this Ghanaian cohort, particularly among younger and unmarried women, but was not significantly associated with ABO. Targeted screening among high-risk groups is necessary, and future molecular approaches may better characterise BV subtypes linked to ABO in African settings.